A simplificação como traço de um habitus tradutório para a Antropologia Brasileira em língua inglesa: um estudo baseado no corpus da oba O Povo Brasileiro de Darcy Ribeiro - Serpa, Talita; Camargo, Diva Cardoso de [UNESP] (My University, 2013)
The main purpose of this article is to investigate the social and linguistic behaviors of a translator, analyzing the use of simplification aspects in the translational process into English of the Anthropology developed by Darcy Ribeiro. With this aim, we used a parallel corpus composed by the work O povo brasileiro (1995) and by its respective translation, performed by Rabassa. The methodology used is that of Corpus-Based Translation Studies (BAKER, 1993, 1995, 1996; CAMARGO, 2005, 2007), Corpus Linguistics (BERBER SARDINHA, 2004) and Terminology (BARROS, 2004). We also adopted Sociology of Translation theories (SIMEONI, 1998, 2007; GOUANVIC,1999, 2005), as well as the habitus conception, proposed by Bourdieu (1980). Results show that this simplification may be found in Ribeiro’s translated texts, indicating the difficulties of conceptualizing the Brazilian universe in English

O objetivo deste trabalho é investigar o comportamento linguístico-social de um tradutor, analisando, para isso, o uso de traços de simplificação no processo tradutório para o inglês da Antropologia desenvolvida por Darcy Ribeiro. Para tanto, nos valemos de um corpus composto pela obra O povo brasileiro (1995); e pela respectiva tradução, realizada por Rabassa. A metodologia foi a dos Estudos da Tradução Baseados em Corpus (BAKER, 1993, 1995, 1996; CAMARGO, 2005, 2007), da Linguística de Corpus (BERBER SARDINHA, 2004) e da Terminologia (BARROS, 2004). Adotamos também a Sociologia da Tradução (SIMEONI, 1998, 2007; GOUANVIC,1999, 2005), e o conceito de habitus, proposto por Bourdieu (1980). Notamos que essa disposição por simplificar pode ser encontrada na tradução do texto de Ribeiro, evidenciando as dificuldades de conceituar o universo brasileiro.
Simplification as an aspect of translational habitus to Brazilian Anthropology in English: a study based on the corpus of the work The Brazilian People written by Darcy Ribeiro
Keywords: Estudos da Tradução Baseados em Corpus; Simplificação; Habitus; Corpus-Based Translation Studies; Simplification; Habitus